Synthesis of New Derivatives of Benzofuran as Potential Anticancer Agents - Napiórkowska, Mariola (Molecules, 2019)
The results of our previous research indicated that some derivatives of benzofurans, particularly halogeno-derivatives, are selectively toxic towards human leukemia cells. Continuing our work with this group of compounds we here report new data on the synthesis as well as regarding the physico-chemical and biological characterization of fourteen new derivatives of benzofurans, including six brominated compounds. The structures of all new compounds were established by spectroscopic methods ((1)H- and, (13)C-NMR, ESI MS), and elemental analyses. Their cytotoxicity was evaluated against K562 (leukemia), MOLT-4 (leukemia), HeLa (cervix carcinoma), and normal cells (HUVEC). Five compounds (1c, 1e, 2d, 3a, 3d) showed significant cytotoxic activity against all tested cell lines and selectivity for cancer cell lines. The SAR analysis (structure-activity relationship analysis) indicated that the presence of bromine introduced to a methyl or acetyl group that was attached to the benzofuran system increased their cytotoxicity both in normal and cancer cells.